Loss of the endothelial glycocalyx is associated with increased E-selectin mediated adhesion of lung tumour cells to the brain microvascular endothelium - Rai, Srijana (J Exp Clin Cancer Res, 2015)
BACKGROUND: Arrest of metastasising lung cancer cells to the brain microvasculature maybe mediated by interactions between ligands on circulating tumour cells and endothelial E-selectin adhesion molecules; a process likely to be regulated by the endothelial glycocalyx. Using human cerebral microvascular endothelial cells and non-small cell lung cancer (NSCLC) cell lines, we describe how factors secreted by NSCLC cells i.e. cystatin C, cathepsin L, insulin-like growth factor-binding protein 7 (IGFBP7), vascular endothelial growth factor (VEGF) and tumour necrosis factor-alpha (TNF-α), damage the glycocalyx and enhance initial contacts between lung tumour and cerebral endothelial cells. METHODS: Endothelial cells were treated with tumour secreted-proteins or lung tumour conditioned medium (CM). Surface levels of E-selectin were quantified by ELISA. Adhesion of A549 and SK-MES-1 cells was examined under flow conditions (1 dyne/cm(2)). Alterations in the endothelial glycocalyx were quantified by binding of fluorescein isothiocyanate-linked wheat germ agglutinin (WGA-FITC). RESULTS: A549 and SK-MES-1 CM and secreted-proteins significantly enhanced endothelial surface E-selectin levels after 30 min and 4 h and tumour cell adhesion after 30 min, 4 and 24 h. Both coincided with significant glycocalyx degradation; A549 and SK-MES-1 CM removing 55 ± 12 % and 58 ± 18.7 % of WGA-FITC binding, respectively. Inhibition of E-selectin binding by monoclonal anti-E-selectin antibody completely attenuated tumour cell adhesion. CONCLUSION: These data suggest that metastasising lung cancer cells facilitate their own adhesion to the brain endothelium by secreting factors that damage the endothelial glycocalyx, resulting in exposure of the previously shielded adhesion molecules and engagement of the E-selectin-mediated adhesion axis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13046-015-0223-9) contains supplementary material, which is available to authorized users.